From bacteria to cancer exploiting metabolic networks for industrial and therapeutic purposes - Tomi Andrino, Claudio (2023)
Metabolic modelling has been used to facilitate industrial microbiology projects and identify potential drug targets for the last 15 years. Although originally modest, the reliability of simulations has greatly improved by the progressive inclusion of chemical, biological and medical information in the models. While the multidisciplinary nature of systems biology entails rich and novel perspectives to solve problems, it is accompanied by a general lack of standardisation and consensus on methodology. Therefore, establishing robust workflows requires (i) assessing and comparing the predictive capabilities of current approaches against experimental data, and (ii) combining the strong points of different strategies to minimize their limitations and generate useful data in a timely manner.